Teaching Vocabulary to Deaf Students Through Enriched Subtitling: A Case Study in Qatar - HAMDY HASSAN, RAGIA; NEVES, JOSELIA (International Journal of Language, Translation and Intercultural Communication, 2019)
This interdisciplinary study examines the impact of using enriched subtitling (ES), within a total communication (TC) holistic approach to language learning, on the acquisition of vocabulary by deaf and hard of hearing (DHH) students. The performance of the students in an experimental class, using an ES-based lesson, was compared to two classes using traditional educational methods, focusing on text reading and sign language. The classes were followed by three tests, one immediately after the class, and two other delayed tests, a day and a week later. Qualitative and quantitative data was collected and triangulated through class observations, student feedback, test results, focus group discussions, and interviews. Test results showed that the experimental class achieved the best results, supporting the research hypothesis that, when integrated in carefully planned lessons, ES can be a valuable tool to enhance vocabulary acquisition by deaf students.